The Role of Vehicle Speed Management in Urban Air Pollutant Emission Reduction - Adyati Yudison; Driejana Driejana; Iman K. Reksowardojo; Aminudin Sulaeman (Institut Teknologi Sepuluh Nopember, 2017)
Lack of mass transit facilities in urban area leads motorcycle to become the most chosen vehicle mode in Indonesia. It accounts for approximately 80% of the total motorized vehicle population. Increasing in motor vehicle population causes traffic congestion and lower traffic speed, hence higher emissions that worsen urban air quality. This paper aims to investigate relationship of vehicle travelling speeds and CO2, CO and HC emission profiles of the typical motorcycle used in Indonesia. Exhaust emissions of 20 motorcycles were tested using autocheck analyzer on idle and speed variations of, 10, 20, 30, 40, 50, and 60 kph on a chassis dynamometer. For idle condition average emission rates of CO2, CO and HC were 0.16, 0.03 and 0.002 g/s, respectively. The results show that the highest CO2 and HC emissions of 82.30 g/km and 0.55 g/km, respectively, found at 10 kph. The lowest emissions were found at 60 kph speed with CO2 emission rate of 27.03 g/km and HC of 0.10 g/km. Carbon monoxide (CO) showed slightly different emission pattern, with 12.85 g/km found at 20 kph and 4.18 g/km at 50 kph. In general, the result shows that the higher the speed the lower the CO2, CO, and HC emissions. Emission profiles indicate that the speed between 30-50 km/h could be recommended as the most suitable traffic speed in urban area to ensure mobility, safety as well as the lowest emissions. The results are valuable as input to transportation management as a part of environmentally sustainable transportation.